Prohibition in Quran: Structure and Meaning - Mardjoko Idris (Sunan Kalijaga: International Journal of Islamic Civilization, 2019)
Quran is the word of Allah written in Arabic. In conveying its message, the Quran uses different sentences, including declarative, imperative, and interrogative sentences. This research will focus on prohibition sentences with analysis of speech acts. Prohibition sentence is a sentence that requires the termination of an act from the interlocutor, from the higher position to the lower one. It is assumed that besides being intended for conventional meanings, the prohibition sentences in the Quran also function as other meanings other than the original meaning, by previously understanding the context that becomes the background of a prohibition. The theory used is pragmatics, especially speech acts. The method used is the refer method and the recording technique. The research of prohibition sentences with pragmatics has obtained two prohibition tools those are sharîh and not sharîh. The prohibition sentences in the Quran are not only used for original meaning but also function as other meanings, such as for the purpose of prayer (do’a), offer (iltimâs), suggestion (irsyâd), continuous (dawâm), information as a result (bayânul 'âqibat), pessimistic (tayîs), threat (tahdîd), calming (i'tinâs), disfiguring (taubîh), and ignoring ('adamul-mubâlah).